Median and Ulnar Neuropathy Assessment in Parkinson’s Disease regarding Symptom Severity and Asymmetry - Nilgul Yardimci; Ozlem Cemeroglu; Eda Ozturk; Gülsüm Gürlü; Esra Şahin; Saliha Bozkurt; Tugba Cengiz; Gulderen Karali; Hasim Cakirbay; Atilla İlhan (Parkinson's Disease)
Background. While increasing evidence suggests comorbidity of peripheral neuropathy (PNP) and Parkinson’s disease (PD), the pathogenesis of PNP in PD is still a debate. The aim of this article is to search the core PD symptoms such as rigidity and tremor as contributing factors to mononeuropathy development while emphasizing each individual patient’s asymmetric symptom severity. Methods. We studied 62 wrists and 62 elbows of 31 patients (mean age 66.48±10.67) and 64 wrists and 64 elbows of 32 age-gender matched healthy controls (mean age 62.03±10.40, p=0.145). The Hoehn and Yahr disability scale and Unified Parkinson’s Disease Rated Scale were used to determine the severity of the disease. Results. According to electrodiagnostic criteria, we confirmed median neuropathy in 16.12% (bilateral in two-thirds of the patients) and ulnar neuropathy in 3.22% of the PD group. While mean age (p=0.003), age at PD onset (p=0.019), and H&Y scores (p=0.016) were significant, tremor and rigidity scores were not. The comparison of the mean indices of electrophysiologic parameters indicated subclinical median and ulnar nerve demyelination both at the wrist and at the elbow in the patient groups where a longer disease duration and mild tremor and rigidity scores are prominent, remarkably. Conclusion. A disease related peripheral neurodegeneration beyond symptom severity occurs in PD.